Discrete palladium clusters that consist of two mutually bisecting perpendicular planes. Issue 25 (15th June 2022) - Kojima, Naoya; Kato, Misaki; Sunada, Yusuke
Abstract : The construction of Pd7 Sn4 and Pd8 Ge6 clusters that consist of two mutually bisecting perpendicular planes was accomplished by the reaction of [Pd(CN t Bu)2 ]3 with Me3 Sn–SnMe2 –SnMe3 or Ge6 Me12 . Abstract : The construction of novel molecules with unprecedented alignments of the constituent elements has revolutionized the field of functional materials. The arrangement of two or more planar subunits in a mutually perpendicular fashion is a frequently encountered approach to produce novel functional materials. Previous examples of such materials can be categorized into two well-investigated families: spiro -conjugated and dumbbell-shaped structures, wherein the two planes are aligned orthogonally via a single atom or an axis, respectively. This article describes a third family: reaction of [Pd(CN t Bu)2 ]3 with Sn3 Me8 or Ge6 Me12 afforded a Pd7 Sn4 cluster and a Pd8 Ge6 cluster that consist of two mutually bisecting perpendicular planes. In the Pd7 Sn4 cluster, the two equivalent Pd5 Sn2 planes share three palladium atoms that include a dihedral angle of 85.6°.